Indicadores de calidad para dos suelos con características vérticas de Entre Ríos (Argentina) = Quality indicators for two soils with vertic characterstics in Entre Ríos (Argentina) - Indelangelo, Nicolás; Wilson, Marcelo German; Tasi, Hugo Armando Alberto (Instituto Universitario de Xeoloxía, 2025)
Nowadays, in the central northern region of Entre Ríos farmers clear forest land, both for cat tle rising and crop production, which generates an important pressure on natural resources. Soil quality constitutes one of the aspects to be considered when evaluating the sustainability of production systems. Sustainability must be evaluated through the variables that represent edaphic properties related to the functions attributed to soil resource. Those variables must be sensitive to changes in the soil use and management. The objective of this research was to select soil quality indicators to obtain a minimum data set (MDS) for two representative soil subgroups and for production systems that characterize the region, as well as to propose mana ging practices for sustainable systems. The two selected soils were a Vertic Ocracualf (Arrúa Series) and an Argic Peludert (Santiago Series). Undisturbed soils sites and different agricul tural histories were defined in each. Superficial samples were taken (0 to 12 cm deep) and che mical, physical-chemical and physical variables were determined. Principal Components Analysis (PCA) and Medium Multiple Comparison (MMC) were performed to select quality indicators for each soil. The PCA BiPlot, the Analysis of Conglomerates and the MMC were used for the analysis of the dynamic change of the soil quality due to agricultural use. Soils were disturbed by continuous agricultural use. A MDS was proposed for each soil, which was similar for both subgroups. Total Organic Carbon (TOC), Total Nitrogen (TN) and Hénin’s ins tability index (Is), integrated the MDS for both soils. Total porosity (TP) was also included in the MDS of the Vertisol. In the Alfisol, where microbiological variables were also determined, microbial biomass carbon (C-biom) and net N mineralization (N-min) were selected as indi cators. By analyzing the meaning of indicators and taking into account the identified deterio ration processes it was possible to identify practices that involve the sequence of agricultural crops in a low proportion and plural-annual pastures as an adequate base for rotation.